Strategi Pemenuhan Bahan Baku Cacing Sutra (Tubifex SP.) untuk Mendukung Kegiatan Pembenihan Ikan di BBI Kabupaten Mesuji - Rama Dewantara; Jan Hotman (Jurnal Enterpreneur dan Bisnis (JEBI), 2026)
Silkworms (Tubifex sp.) are a natural feed that plays a crucial role in fish hatchery activities due to their high protein content and easy digestion by fish larvae. The sustainable availability of silkworms is crucial for the success of fish seed production at the Mesuji Regency Fish Seed Center (BBI). However, various obstacles remain in its implementation, such as supply instability, dependence on suppliers from outside the region, price fluctuations, and the risk of quality degradation during the distribution process. This study aims to analyze the condition of silkworm raw material fulfillment, identify the obstacles faced, and formulate strategies that can be implemented to support fish hatchery activities at the BBI in Mesuji Regency.The study employed a qualitative descriptive method. Data were obtained through observation, interviews, and documentation. The informants consisted of managers and technicians from the Mesuji Regency Fish Seed Center (BBI) involved in fish hatchery activities and silkworm procurement. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing.The results indicate that silkworms are the primary natural food used in the larval stage of fish and play a crucial role in increasing the growth and survival rate of fry. The main obstacles faced in fulfilling silkworm needs include unstable supply availability, dependence on external suppliers, and fluctuations in price and quality. The strategies implemented by the BBI Mesuji Regency include collaboration with several suppliers, feed requirement planning, silkworm use management, and quality control. The most potential strategy to support the sustainability of fish hatchery activities is the development of independent silkworm cultivation to ensure supply continuity, improve natural food quality, and reduce dependence on external suppliers.